SUATU TELAAH TENTANG KEBERADAAN ANAK SUMBANG DALAM MEWARIS DI LIHAT DARI ASPEK HUKUM ADAT. - Iman Hidayat (Universitas Batanghari Jambi, 2015)
Custom is the reflection of personality and is one of the reflections of nation soul from century to century. Every nation in the world has its own custom which is not similar from one another, depending on the place and the time. This difference is the most important aspect as the identity of a nation.The level of civilization, or the modern way of life is not able to eliminate the custom that is found in indigenous society. In the process of the advancement of the era, the custom adapts itself in accordance with the advancement of the society.Keyword: Existence of traditional Institutions